Medieval Latin and Middle English literature essays in honour of Jill Mann - Mann, Jill 1943-; Cannon, Christopher; Nolan, Maura (Boydell & Brewer, 2011)
Jill Mann's writing, teaching, and scholarship have transformed our understanding of two distinct fields, medieval Latin and Middle English literature, as well as their intersection. Essays in this volume seek to honour this achievement by looking at entirely new aspects of these fields (the relationship of song to affect, the political valence of classical allusion, the Latin background of Middle English devotional texts). Others look again at the literary kinds and ideas most important in Mann's own work (beast fable, the nature of allegory, the nature of 'nature', the relationship of economic thought and literature, satire, language as a subject for poetry) in the poets she has been most drawn to (Chaucer, Langland, Henryson). All of the essays involve close readings of the most careful kind, taking as their primary method Professor Mann's repeated injunction to attend, above all, to the 'words on the page'. Christopher Cannon is Professor of English, New York University; Maura Nolan is Associate Professor of English, University of California, Berkeley. Contributors: Siobhain Bly Calkin, Christopher Cannon, Rebecca Davis, Peter Dronke, A.S.G. Edwards, Elizabeth B. Edwards, Maura Nolan, Paul J. Patterson, Derek Pearsall, Ad Putter, Paul Gerhard Schmidt, James Simpson, Barry Windeatt, Nicolette Zeeman